Promoción turística para el posicionamiento del distrito de Lunahuaná como destino turístico nacional, 2022 - Mencia Rojas, Jenyffer Marlene (2024)
The objective of this research is to determine the relationship between tourism promotion and the positioning of Lunahuaná as a tourist destination in 2022. The approach is quantitative, a non- experimental, descriptive and correlational design is used. The survey was applied as a technique and with a questionnaire as an instrument, data was collected on the dimensions of tourism promotion : advertising, support materials, public relations and positioning: functional, symbolic, experiential, from a representative sample of 166 tourists. The applied instruments were subjected to expert judgment and reliability through Crombach's alpha, reaching high reliability values of 0.909 and 0.857. The results reveal a significant relationship supported by a p-value of 0.000, rejecting the null hypothesis. Spearman's Rho correlation coefficient of 0.452 confirms a medium positive correlation between the variables, the same occurs with the specific hypotheses raised. It is concluded that intensifying tourism promotion in Lunahuaná boosts its positioning as a tourist destination. It is recommended to consolidate continuous strategies, adaptation to market feedback, local alliances, monitoring of key indicators and periodic evaluation of the impact, ensuring a sustainable and successful tourism presence in the long term.